2021
DOI: 10.3390/metabo11090629
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Isolation of Broad-Spectrum Fungicidal Active Compound from Artemisia ordosica

Abstract: To avoid the widespread resistance of commercial fungicides, new broad-spectrum botanical fungicides need to be developed. In previous bioactive screening assays, extracts of Artemisia ordosica Krasch. (A. ordosica) had highly antifungal activities, but the responsible phytochemicals were unidentified. In this study, active compounds of A. ordosica extracts were identified using a bioassay-guided method, and antifungal assays were performed in vitro and in vivo. The bioactive compounds were dissolved in petrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…[7,8,9] Currently, the focus of research on plant-derived fungicides primarily revolves around the identification of antifungal bioactive compounds sourced from plants or the extraction and structural modification of their active ingredients to facilitate the discovery and development of novel pesticides. [10,11] Nootkatone, a sesquiterpenoid compound, was isolated and identified from the heartwood of Alaska yellow cedar. In addition, Nootkatone is widely used in food, pharmaceutic and pesticidal industry because of their different bioactivities, including antimicrobial, antioxidant, anti-inflammatory and insecticidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8,9] Currently, the focus of research on plant-derived fungicides primarily revolves around the identification of antifungal bioactive compounds sourced from plants or the extraction and structural modification of their active ingredients to facilitate the discovery and development of novel pesticides. [10,11] Nootkatone, a sesquiterpenoid compound, was isolated and identified from the heartwood of Alaska yellow cedar. In addition, Nootkatone is widely used in food, pharmaceutic and pesticidal industry because of their different bioactivities, including antimicrobial, antioxidant, anti-inflammatory and insecticidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…A. ordosica contains many bioactive compounds, which encompass polyphenols, flavonoids, terpenoids, essential oil and polyacetylenes (Zhang et al, 2017;Wang et al, 2019;Zhou et al, 2019). Numerous studies have demonstrated that A. ordosica has anti-inflammatory, antimicrobial (Xiao et al, 2020;Tang et al, 2021), antioxidant (Wu et al, 2019) and immunoregulatory (Xing et al, 2019) properties. Previous reports have indicated the potential benefits of A. ordosica aqueous extract (AOE) as a natural phytogenic feed additive with antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%